ANALISIS SUMBERDAYA KEUANGAN DI MASA PANDEMI COVID-19 DI PT. JASAMARGA TOL BALI MANDARA - Putu Sugi Kurnia Dewi; I Dewa Made Sutedja (Majalah Ilmiah Widyacakra, 2020)
ABSTRACT The pandemic Covid 19 that first appeared in China, to be precise in the city of Wuhanaround December 2019 and has spread throughout the world, including in the Republic ofIndonesia, which we love, entered in early March 2020 until now it continues to increasefrom the number of positive sufferers and is also significantly related to the rate of recoveryThe impact on the disruption of various activities in the community as a result of theimposition of distance restrictions and human gathering will certainly have an impact on allsectors including the tourism economy sector which is the foundation for life in Baliespecially and Indonesia in general. The purpose of the final partial analysis during thispandemic is to be able to find out the financial position by using several ratios in financialanalysis and comparing between the first semester before the pandemic and the first semesterduring the pandemic, the results of the financial position at PT Jasamarga Tbk as themanager of the Bali Mandara Toll Road have decreased in terms of power. The ability of thiscan be seen in the liquidity ratio, leverage ratio and profitability ratio, but from anoperational point of view it is still and has been able to provide good public services to thepublic during the pandemic Covid 19.